PEMBERIAN REBUSAN DAUN SIRIH MERAH TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI KLINIK BIDAN FINA SEMBIRING KECAMATAN MEDAN POLONIA - Maximilianus Dasril Samura; Mela Azrianti (INSTITUT KESEHATAN DELI HUSADA, 2021)
Every mother who has completed childbirth and received services that are in accordance with postpartum maternal service standards is called postpartum maternal health services. The standard that must be followed by postpartum mothers to get these services is at least 3 (three) times, ie six hours after delivery until three days later. After that, on the fourth day until the 28th day, then on the 29th day until the 42nd day after the labor period is over. So it can be interpreted that the postpartum period is the period after six hours of delivery until the 42nd day after delivery The purpose of this study was to determine the effect of red betel leaf decoction on perineal wound healing in postpartum mothers at the Fina Sembiring Midwife Clinic, Medan Polonia District. This study used a quasi-experimental design with the Pre-Post Test Two Group Design, which was to see the difference between the intervention group and the control group. The population in this study were 10 respondents. In this study using the Independen Sample T Test. The results showed that there was a difference between before and after being given boiled betel water, namely 1,300 with Std. Deviation 1.031 with 95% CI = 817-1.783 with p value = 0.000. The conclusion of this study is that there is an effect of red betel leaf decoction on perineal wound healing in postpartum mothers at the Fina Sembiring Midwife Clinic, Medan Polonia District.